USING TASK-BASED LANGUAGE TEACHING TO TEACH TENTH GRADERS OF SMA NEGERI 9 SURABAYA TO ANALYZE SIMPLE PAST AND PAST CONTINUOUS TENSE IN RECOUNT TEXT (RETAIN, 2014)
USING TASK-BASED LANGUAGE TEACHING TO TEACH TENTH GRADERS OF SMA NEGERI 9 SURABAYA TO ANALYZE SIMPLE PAST AND PAST CONTINUOUS TENSE IN RECOUNT TEXT LUFI WIRMARINI LUKMAN English Education, Language and Art Faculty, State University of Surabaya lovaluffy@yahoo.co.id ESTI KURNIASIH, S.Pd., M.Pd. English Education, Language and Art Faculty, State University of Surabaya estikurniasih87@yahoo.com Abstrak Siswa-siswi kelas X, dalam kurikulum 2013, diharapkan mampu menganalisis unsur kebahasaan dalam teks recount, termasuk struktur bahasanya, atau grammar. Mengajar grammar umumnya terdiri dari menjelaskan formula disertai dengan memberi contoh penggunaannya. Namun, hal ini terkadang belum mencukupi kebutuhan siswa dalam pembelajaran grammar, terutama agar mereka berkompeten dalam menganalisis kalimat dan mampu menerapkan rumusan kalimat tersebut dalam berbagai konteks. Guru hendaknya mampu memastikan bahwa siswa benar-benar telah mencapai kompetensi analisis yang diharapkan. Adapun pendekatan pembelajaran yang dapat menjadi solusi pengajaran yang tepat, yaitu Task-Based Language Teaching (TBLT). Pada prinsipnya, TBLT adalah memberi tugas pada siswa hingga mereka mencapai target pembelajaran, dalam hal ini adalah penggunaan grammar yang tepat. Penelitian ini adalah sebuah studi kualitatif, dengan dua objektif, pada kelas X IPA 3 SMA Negeri 9 Surabaya. Objektif penelitian ini adalah untuk menggambarkan penerapan TBLT untuk mengajar siswa untuk menganalisis simple past dan past continuous tense dalam teks recount dan untuk mencatat respon siswa terhadap implementasi pengajaran tersebut. Instrumen penelititan terdiri dari observasi, field note, dan kuesioner. Data mengenai implementasi pengajaran dikumpulkan menggunakan observasi dan field note, sedangkan data respon siswa dikumpulkan dengan kuesioner. Data penelitian yang didapat menggambarkan bahwa guru mengimplementasikan tugas yang sama dengan tiga teks yang berbeda dalam tiga pertemuan. Langkah-langkah pembelajaran terdiri dari mengamati, mempertanyakan, mengeksplorasi, mengasosiasi, dan mengkomunikasikan. Guru tersebut memandu siswa untuk melakukan aktivitas pembelajaran secara berurutan, seperti yang telah dirancang dalam Kurikulum 2013. Pemberian tugas dilakukan dalam tahap mengeksplorasi, dimana siswa diminta untuk menganalisis kalimat simple past dan past continuous dalam teks yang diberikan. Implementasi TBLT ini berjalan dengan baik dan menghasilkan respon yang positif dari siswa. Dari deskripsi data, dapat disimpulkan bahwa pendekatan TBLT dapat memfasilitasi siswa untuk belajar menganalisis kalimat simple past dan past continuous tense dalam teks recount. Implementasi tersebut didasari oleh prinsip mengenai tahap pembelajaran Bloom, dari kemampuan memahami hingga menganalisis, dan tahap pembelajaran yang dirancang dalam Kurikulum 2013, dari kegiatan mengamati hingga mengkomunikasikan. Implementasi ini dapat dijadikan sebagai referensi pengajaran grammar bagi guru-guru lain, peneliti, maupun guru sebagai peneliti. Kata Kunci: Task-Based Language Teaching (TBLT), pendekatan pembelajaran, analisis, simple past dan past continuous tense, teks recount, respon siswa Abstract Tenth graders in Indonesia are supposed to be able to analyze linguistic components in recount text, including grammar, outlined in the 2013 Curriculum. Teaching grammar usually includes explaining the rules and providing some examples. However, this may be inadequate to enable the students to analyze the examples and therefore to use the grammar rules appropriately in different conditions. Teachers need to assure that the students genuinely learn in order to accomplish that objective. Task-Based Language Teaching (TBLT) approach is a preferrable teaching resolution. It provides exercises to the students, aimed to teach the students the accurate use of grammar. This study was a qualitative study, with two objectives, on X IPA 3 of SMA Negeri 9 Surabaya. The objectives are to describe the implementation of TBLT to teach the students to analyze simple past and past continuous tense in recount text and to record the students’ responses toward it. The instruments are observation checklist, field note, and questionnaire. The data of how the teacher implemented the approach were collected using observation checklist and field note, and the students’ responses were recorded using a close-structured questionnaire. The data obtained described that the teacher applied the similar task using three different texts in three meetings. The class was facilitated to have learning in five steps: observing, questioning, exploring, associating, and communicating. The teacher guided the students to do each step chronologically as outlined in the Curriculum of 2013. Tasks were given in exploring activity that the students were asked to analyze simple past and past continuous sentences in the text given. The implementation of TBLT to teach the students to analyze simple past and past continuous tense in recount text was running well and resulted positive responses of the students. In conclusion, TBLT approach is useful to enable the students to analyze simple past and past continuous tense in recount text. The implementation was based on the learning steps of Bloom from understand to analyze and the learning steps of the 2013 Curriculum from observing to communicating. Teachers could, at least, view this as a good choice for teaching grammar. Researchers or teachers as researchers, on the other hand, could make use of this study to develop further investigation on grammar teaching and learning using TBLT approach. Key words: Task-Based Language Teaching (TBLT), approach, analyze, simple past and past continuous tense, recount text, students’ response INTRODUCTION Tenth graders are supposed to learn some genres of text, including recount. This includes mastery of both the language skills and components. The language skills are listening, speaking, reading and writing while the supporting components are vocabulary, grammar and pronunciation. Grammar is one of the language components on which some teachers may put more concern. There is a view of students that considers grammar as a means to self-sufficiency (Savage, Bitterlin, & Price, 2010). Long (2000) mentioned that teaching grammar usually includes explaining the rules and providing some examples. Teachers can begin by introducing the grammar topic to the students. It continues with the explanation of when and how to apply the rules. The last step of this basic teaching is to provide examples. However, that way of teaching may be inadequate to activate awareness of students of what are beyond grammatical structure. They are form, meaning and use (Larsen-Freeman, 2001). Savage et al. (2010) explains that students may make mistakes even if they create sentences with correct structure. As an example, it is too formal to use “I must go” while speaking because the use of “must” is much more in writing than speaking. This implicates that teaching grammar is not merely of enabling learners to use the rules for one but some different conditions. Another urgency that raises is that teachers are to guide tenth graders to be competent of grammar in the stage of analyze. Analyze has surely passed three previous cognition stages, that are know, comprehend, and apply (Bloom, 1956). It demands the teacher, teaching to analyze grammar, to plan activities that most probably guide the students to form the grammar rules in their mind. This will probably be solved by providing exercises to the students. Tasks activity is the core of an approach, namely Task-Based Language Teaching (Long, 2000). Long (2000) mentioned Task-Based Language Teaching (TBLT) as an approach which considers that language learning happens through performing in tasks, for tasks aim to give learners opportunities to reinforce what they have just learnt. This is supported by Ellis (1994), from some studies of Second Language Acquisition (SLA) faculty, that repetitions in grammar teaching result in accurate use of grammar. Further considerations for the practice including the amount of exercises depend on the students need (Nunan, 1995). The process of teaching students to analyze simple past and past continuous tense in recount text within TBLT is one point that may fill a rift in the interrelated sources gained. The researcher traces for the description in a class of SMA Negeri 9 Surabaya, X-IPA-3. The result, directly after that, will also be discussed to show how the TBLT practice works. Task-Based Languaged Teaching (TBLT) has been practised and studied in either EFL or ESL teaching and learning. A study of the TBLT implementation on an ESP class was one of the sources. It was conducted by Hyde (2013), entitled “Task-Based Language Teaching in the Business English Classroom”, to improve the students’ performance. The students were taught Business English using present-practice-produce (PPP) method. Hyde (2013) found that TBLT is an excellent approach to teach Business English comparing to PPP. Another study on Task-Based Language Teaching (TBLT) was conducted by Choo & Too (2012), entitled “Teachers’ Perceptions in Using Task-Based Instruction (TBI) for the Teaching of Grammar”. Choo & Too (2012), however, mentioned TBLT as Task-Based Instruction (TBI). The study aims to trace for teachers’ opinions towards the implementation of TBI for grammar teaching. The subjects are eight EFL teachers from a Chinese private school. The result of the study is that, although not all teachers expressed TBI as a suitable approach in their grammar classes, they concurred that it is a preferrable alternative approach for grammar teaching. The two studies show that Task-Based Language Teaching (TBLT) gives positive contribution for English learning, either for specific purposes or for the language mastery. For this reason, the researchers were triggered to conduct a study on TBLT practice in another case. If Choo & Too (2012) recorded the teacher’s opinions toward TBLT, and Hyde (2013) made use of TBLT for improving a Business English class learning, the researchers aimed to describe the implementation of TBLT to teach to analyze recount text, primarily the grammatical forms as the materials. This study outlines two research questions, “How is the implementation of Task-Based Language Teaching to teach tenth graders of SMA analyze simple past and Negeri 9 Surabaya to past continuous tense in recount text?” and “How do the students respond toward the implementation of Task-Based Language Teaching to teach them to analyze simple past and past continuous tense in recount text?” A point to be noted is that this implementation was done with the syllabus of the 2013 Curriculum. It is outlined that the students would be having activities with scientific approach, a set of learning that consists of five major steps, observing, questioning, exploring, associating, and communicating. METHODOLOGY This research is a qualitative study. A type of qualitatative study, known as basic interpretative study, is aimed to describe a phenomenon and to develop plausible explanations in regard to interpret the phenomenon (Ary, Jacobs, Sorensen, & Razavieh, 2010). The subjects of the study are the teacher and the students of X IPA 3 SMA Negeri 9 Surabaya. The data obtained are divided into two parts. The first data are to answer the first research question. It is the implementation of TBLT to teach the students to analyze simple past and past continuous tense in recount text, including the teacher’s actions and the students’ learning activities, collected using observation checklist and fiel note. The second data are the students’ responses toward the implementation, collected using a close-structured questionnaire. The close-structured questionnaire consists of 9 questions, asking opinions toward the learning topic, the learning indicators, and the learning progress of the students. The data were analyzed in descriptive manner. Analyzing qualitative research consists of organizing and familiarizing, coding and reducing, and interpreting and representing (Ary, et al., 2010). The researcher firstly tried to organize the data into two categories, the data that are likely for the first and the other ones for the second research question. Secondly, the researcher sorted the data to code and reduce it. This is to precisely categorize the data based on the research questions. Finally, the researcher did steps of interpreting and representing. Interpretation is bringing out the meaning, telling the story, providing an explanation and developing plausible explanations, while representation is about how the data are presented (Ary, et al., 2010). This leads the researcher to firstly provide the description of the data and at the same time bring some elaboration referred to related theories and findings developed. RESULT AND DISCUSSION Result The three-day-implementation was on 7-8 period of the school time. It began at 11.20 and ended at 12.50 a.m. The teacher implemented TBLT for grammar teaching, simple past and past continuous tense, in recount text, using four texts as the materials. The students actively participated in the class. They passed activities guided by the teacher in five major steps, observing, questioning, exploring, associating, and communicating. Observing includes understanding the gist of the text. Some students read sentences in the text loudly while some other were listening to the spoken text. After that, teacher asked the students to identify simple past and past continuous sentences in the text. It was recorded that the students questioned about recount text, what makes it different from other kinds of text, how events are described in recount, and how recount would appear in Indonesian. The third activity is exploring. The students were analyzing the two forms in groups. They were asked to classify each word or phrase of the sentences in the text given into its function and to transform the sentence pattern, such as from positive into negative and interrogative. The students did the task with the aids of group discussion but were going to submit the work individually. Fourthly, the students did peer correction with another group and for had a whole class discussion guided by the teacher for negotiating the best answer in associating activity. At the last, the students concluded what the text tells them about in detail. It was communicating activity, by which they communicate their understanding about the text after thoroughly analyze each of the sentences. In the step of observing, the teacher found some errors of the students’ in proonunciation when they were reading the sentences aloud. The teacher gave feedback to correct them. The students were also checking dictionary for some less familiar words, thus they could understand what the text tells them about. The questioning step had been passed subconsciously by the students. Some students asked to the teacher about recount text. The teacher invited the whole class to try to answer. It led to a short discussion of the whole class. The students, while trying to get the best answer, were formulating questions in their mind about recount text. the teacher turned down only to justify their ideas. In exploring stage, the students were doing the task of analyzing the sentences in the text. there were about 15 sentences to deal with. The task consists of classifying each word or phrase into its function and to transform the sentence pattern, such as from positive into negative and interrogative. The students did it cooperatively in groups as they had some discussion with their mates. However, each student wrote their own work on a piece of paper. The task is to be submitted individuallly. The students associated their work with others’ and with the teacher’s comments in associating step. The teacher gave them time to do peer correction with another group. After that, he led a whole class discussion to negotiate for the best answers. He gave the students time to correct their work, based on the feedback. The last step is communicating. The teacher invited the students to mention what the text tells them about. the students were supposed to mention any details of the events in the text. This was aimed to review thei understanding about the text after analyzing each of the sentences. The 39 students of X IPA 3 had four recount texts as the learning materials, all of which use simple past and past continuous tense and tell plausible events to the students. The titles of the texts are “Camping”, given in the first meeting, “My Grandpa’s Birthday” and “Holiday in Gunung Penanggungan”, given in the second meeting, and “My Holiday was Fantastic”, for the last meeting. After the implementation ended, the teacher passed the close-structured questionnaire to each student. There were 38 students as the respondents. Most of the students stated that grammar is difficult but important to learn. They also stated that the tasks helped them to pass the learning indicators and to progress learning simple past and past continuous tense from the first to the second meeting, and from the second to the third meeting. Discussion The implementation was done by the teacher in five steps. The teacher led the class to have observing, questioning, exploring, associating, and communicating in the three meetings. The teacher did, as what Vacca (1981) suggests, managing the class to do the task in groups. He also told the class to report their work individually. He conducted some discussions with the whole class about the work to do some correction. The teacher even made use of the three activity kinds offered by Vacca (1981), individual, small-group discussion, and whole class work. The other thing was that the teacher gave additional scores for whoever participating in the class discussion. That was a creative way of conducting a class, which Oller (1983) stated could maintain high student interest. Analyzing stage, according to Bloom (1956), has three previous stages of cognition, those are know, comprehend, and apply. The teacher had conducted activities for the three cognition process before he asked the students to do the analyzing task. The activities were reading the text for knowledge stage, observing the text for understanding the meaning, and observing simple past and past continuous sentences in the text while also questioning how events are described in recount text and how the text used in Indonesian for application process. The class had done the work of analyzing simple past and past continuous sentences in the recount texts given, which inferred that they had also successfully passed the first four stages of cognition process on the topic. More importantly, the teacher had implemented more than one concept of learning for his teaching program. He utilized taxonomy of Bloom (1956) and scientific approach, outlined by the government for the 2013 English teaching Curriculum, which includes steps of observing, questioning, exploring, associating, and communicating, together with Task-Based Language Teaching (TBLT) approach. The teaching implementation had gained the students’ responses. Most of them agreed that the tasks given enabled them to progress learning about simple past and past continuous tense in recount text from meeting to meeting. It was likely the transformation drills that enabled the students to analyze simple past and past continuous sentences in the recount texts given well, as what Stevick (1982) noted. The task of classifying words or phrases in the sentences was aimed to help the students more aware of parts of speech used and therefore to transform the sentences from positive into negative and interrogative. The teacher got benefits combining taxonomy of Bloom (1956) with the learning steps outlined in the most recent English teaching curriculum, the Curriculum of 2013 in the implementation. On the other hand, the students did respond positively toward the approach of TBLT, that they were helped to achieve the learning goal through doing the tasks. Gratitudes The researchers is in much debt for this study accomplishment. They would like to thank to the school on which this study was conducted. They also would like to thank to State University of Surabaya for allowing this study published. CONCLUSION AND SUGGESTIONS Conclusion Regarding to the research questions, there are two things to be concluded: The implementation did run well. There were five steps of learning outlined in the 2013 Curriculum, known as scientific approach, implemented with the learning objective from know to analyze. TBLT approach is useful to enable the students to analyze simple past and past continuous tense in recount text. The students’ responses toward the implementation, in the highest amount, were positive. They said that they could attempt to understand, identify, classify, and transform simple past and past continuous sentences in the recount texts given easily through doing the tasks. They also stated that the tasks enabled them to progress learning the two forms from the first meeting to the second, and from the second to the third. Suggestions Teachers could see this as a reference that TBLT approach is applicable for grammar teaching. On the other hand, researchers could make use of this descriptive study to develop any further investigation. Teachers as researchers could also gain this finding to make improvements in grammar teaching and learning. REFERENCES Ary, D., Jacobs, L. C., Sorensen, C., & Razavieh, A. (2010). Introduction to Research in Education. Wadsworth: Cengage Learning. Bloom, B. S. (Ed.). (1956). Taxonomy of educational objectives: The classification of educational goals. New York: Longman. Ellis, R. (1994). The Study of Second Language Acquisition. Oxford: Oxford University Press. Hyde, C. (2013). Task-Based Language Teaching in the Business English Classroom. Master, University of Wiconsin, River Falls. Larsen-Freeman, D. (Ed.). (2001). Teaching English as a Second or Foreign Language, Third Edition. Boston: Heinle & Heinle. Long, M. H. (2000). Focus on Forms in Task-Based Language Teaching. Langauge Policy and Pedagaogy: Essays in Honor of A. Ronald Walton(10). Nunan, D. (1995). Closing the Gap Between Learning and Instruction. TESOL Quarterly, 29(1), 133-158. Oller, J. W., & Richard-Amato, P. A. (1983). Methods that work: A smorgasbord of ideas for language teachers. Cambridge: Newbury House Publishers. P.L., J. C., & Too, W. K. (2012). Teachers’ Perceptions in Using Task-Based Instruction (TBI) for the Teaching of Grammar. Journal of Interdisciplinary Research in Education (JIRE), 2(1). Savage, K. L., Bitterlin, G., & Price, D. (2010). Grammar Matters: Teaching Grammar in Adult ESL Programs. Cambridge: Cambridge University Press. Stevick, E. W. (1982). Teaching and Learning Languages. Cambridge: Cambridge University Press. Vacca, R. T. (1981). Content Area Reading. Boston: Little, Brown and Company Limited.